Efficacy of inosine pranobex as an adjuvant oral therapy in anogenital warts: an evidence-based case report - Nelson, Benny; Sastrini, Indina; Anissa, Lidwina; Manalu, Patricsia; Fourina, Peppy; Kuraga, Rahmaniar Desianti; Indriatmi, Wresti (UI Scholars Hub, 2019)
Background: Human papillomavirus (HPV) causes the most prevalent sexually transmitted infection and is an important etiological factor in genital cancer. HPV infection manifests in broad spectrum, from genital warts to cervical intraepithelial neoplasia and cancers. Genital warts remain a frequent problem in primary care. Current modalities provide unsatisfactory result in curing genital warts completely. To date, there are many convincing studies encouraging oral inosine pranobex as an adjuvant therapy to improve post-conventional therapy cure-rate. Aim: To assess the efficacy of inosine pranobex as an adjuvant oral therapy in anogenital warts. Methods: Literature search was performed using Pubmed, Ebsco and Science Direct database. Inclusion criteria were human subjects, randomized controlled trial on patients with genital warts, and inosine pranobex as adjuvant therapy. The studies were appraised and findings were formulated to find the best evidence for collating recommendations in treating genital warts patients. Results: There were three articles related to the clinical questions. All articles were found to be valid after selection based on exclusion and inclusion criteria. Discussion: All articles recommended the addition of oral inosine pranobex as an adjuvant therapy in treating patient with genital warts. Based on the critical appraisal performed previously, addition of oral inosine pranobex may minimize conventional therapy failure. Conclusion: Based on the best evidence available, we would recommend the addition of oral inosine pranobex as adjuvant for treating genital warts, except in special conditions, such as for patients with financial problem as this therapy was not covered by national health insurance.